Development of primer set for the identification of fish species in surimi products using denaturing gradient gel electrophoresis. (September 2017) - Noh, Eun Soo; Park, Yeon Jung; Kim, Eun Mi; An, Cheul Min; Park, Jung Youn; Kim, Kyoung-Ho; Song, Jung-Hun; Kang, Jung-Ha
Abstract: The purpose of this study was to develop a DNA marker for the identification of fish species in processed surimi products. A DNA marker was designed based on the mitochondrial cytochrome c oxidase subunit I gene, and fish species in surimi products were identified using a molecular fingerprinting technique, denaturing gradient gel electrophoresis (DGGE); the results were subjected to sequence-based analysis. The DGGE profiles indicated the presence in surimi products of a greater diversity of fish species than reported previously: 20 species belonging to 16 genera were identified. Therefore, our method facilitates the simple and rapid detection and identification of fish species in seafood products produced from minced fish. Highlights: Efficient marker was developed to identify the fish species from processed food. A method for the identification of fish species using DGGE has been developed. DGGE profiles revealed the presence of a variety of fish species in surimi products.